Information Science: Epistemology and Complexity - Cruz Quiroga, Luis Fernando (2014)
Background Information Science has had little theoretical production and unclear epistemological foundation. Although epistemological orientations have evolved from explanatory to interpretive approaches (systemic, cognitive and social), they have not delved into the complexity of the subject and the object of study. Therefore, they have not responded to investigative needs in information science. Purpose The purpose of this article was to propose an epistemological orientation that took into account the complexity of the subject and the object of study to optimize research in Information Science, and thus, theoretical production. Design It was developed in three phases: First, a historical review of the science to date was conducted, with an emphasis on information, in order to understand the basics of Information Science. Second, a documentary analysis was made on Information Science, since its inception to date, with its different epistemological orientations; and third,a contrast with the research experience of SCED-ISTEC and the University of South Florida USF was effected. Results An epistemological orientation was proposed to support research in Information Science from Complex Systems based on Trans-Disciplinarity Conclusions To meet the needs and challenges of the twenty-first century, research in Information Science requires epistemological orientations that consider the complexity of the subject and the object of study. Therefore, inter / trans-disciplinary research in Information Science requires epistemological foundations that are coherent with the complexity of the subject matter